Austen After 200
XXI, 257 p. 6 illus.
Keywords: “An engaging collection of voices commemorate the first two centuries of Austen’s reception in this volume. These essays share a commitment to level academic and public discourse on Austen and to embrace Austen’s multimedia legacy.” – Inger S. B. Brody, Associate Professor of English and Comparative Literature, University of North Carolina at Chapel Hill, USA Austen After 200 explores our contemporary relationship with Jane Austen in the wake of the bicentenaries of her death and the first publication of her novels. The volume begins by looking at Austen’s popular appeal and at how she is consumed today in diverse cultural venues such the digisphere, blogosphere, festivals and book clubs. It then offers new approaches to the novels within various critical contexts, including adaptation studies, fan fiction, intertextuality, and more. Collecting these new essays in one volume enables a unique view of the crossovers and divergences in engagements with Austenin different settings, and will help a comparative approach between the popular and the academic to emerge more fully in Austen studies. The book gathers insights from a range of contributors invested in new reading spaces in order to show the creative ways in which we are all adapting as we continue to read Austen’s works. Kerry Sinanan is Assistant Professor of Transatlantic Eighteenth and Nineteenth-Century Literature at the University of Texas at San Antonio, USA. She has published on Jane Austen and Barbara Pym, and many articles on Black Atlantic texts, including The Woman of Colour (1808). Annika Bautz is Professor of Nineteenth-Century Literature at the University of Plymouth, UK. Her publications include books and essays on Jane Austen, Walter Scott and Edward Bulwer-Lytton, and on the history of the book in the Romantic and Victorian periods. Daniel Cook is Reader in English at the University of Dundee, UK. He is the author ofThomas Chatterton and Neglected Genius, 1760-1830 (2013), Reading Swift's Poetry (2020), and Walter Scott and Short Fiction (2021).